THE INTERFACE NATURE OF LEXICOGENESIS: WORD FORMATION AND SOME OF ITS INTERCONNECTIONS WITH GRAMMATICALIZATION, PHILOLOGY AND SYNTAX (Muitas Vozes, 2021)
In this paper, some reflections on the multifaceted characteristic of word formation are outlined, a (morph)-lexical semantic phenomenon that is structured as a network of connections between practically all levels/spheres of language, which generates its relevance as an investigative object (primordial or tangential) for different fields of studies on linguistics, notably to those of lexicological and morphological order. With an emphasis on the phenomenon of prefixation — and adopting as general theoretical-epistemological compasses some principles of Complexity theory (CAPRA, 1997; MORIN, 2003; ECO, 2013), systemic thinking (KASPER, 2000; VASCONCELLOS, 2002) and the Multisystemic language approach (CASTILHO, 2002, 2003, 2007, 2009, 2010, 2011; MÓDOLO; BRAGA, 2012) —, it will be sought to unravel ways of contact between morphological lexicogenesis and grammaticalization flows, syntax (articulation of clauses), going through interconnections established with Philology.